1996
DOI: 10.1016/0014-5793(96)00705-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glutathione biosynthesis in the ischemic‐reperfused rabbit myocardium

Abstract: Non-protein thiols (NP-SH) and the activities of the glutathione status-regulating enzymes y-glutamylcysteine synthetase (G-GCS), y-glutamyl transpeptidase (G-GT) and gintathione reductase (GR) were assessed in perfused rabbit hearts subjected to severe (60 rain) or mild (7 min) total ischemia and 30 rain reperfusion. Severe ischemia significantly decreased NP-SH, which were further depressed on reperfusion together with a significant decline in G-GCS activity; G-GT and GR activities were unchanged. Specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Intracellular GSH scavenges ROS, which is an important cell-protective mechanism under the conditions with enhanced oxidative stress (30)(31)(32)(33)(34). In the present study, the effects of ebselen on the tissue contents of GSH were expressed in the endocardial as well as the epicardial side, transmurally (Table 2).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Intracellular GSH scavenges ROS, which is an important cell-protective mechanism under the conditions with enhanced oxidative stress (30)(31)(32)(33)(34). In the present study, the effects of ebselen on the tissue contents of GSH were expressed in the endocardial as well as the epicardial side, transmurally (Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…Activity of glutathione reductase (GR) has been found to be increased by ebselen (35), which is a potential mechanism of GSH preservation by ebselen. More importantly, it has been reported that GSH synthesis is impaired (30,31,33,34), and the activity of γ-glutamylcysteine synthetase (GGCS), a rate-limiting enzyme in GSH biosynthesis, is decreased in I/R (32). The gene encoding GGCS contains an AP-1 site (36, 37), a key region for activating transcription, which is known to be activated by extracellularsignal-regulated kinase (ERK) (38).…”
Section: Discussionmentioning
confidence: 99%
“…The non‐selective K ATP blocker glibenclamide partially antagonized the beneficial effects of both S ‐diclofenac and NaHS in myocardial ischaemia–reperfusion damage. This seems to indicate that H 2 S, released in sufficient amounts by both S ‐diclofenac and NaHS, not only may have overcome the reduced production of H 2 S in ischaemic cardiomyocytes ( Lapenna et al , 1996 ), but may have also triggered a signalling mechanism similar to that described for metabolic ischaemic preconditioning, where activation of sarcolemmal (and not mitochondrial) K ATP play an important role ( Gross and Peart, 2003 ; Bian et al , 2006 ; Johansen et al , 2006 ). However, additional mechanism/s involved in the cardioprotection provided by S ‐diclofenac may not be ruled out.…”
Section: Discussionmentioning
confidence: 92%
“…GPX removes H 2 O 2 by coupling its reduction to H 2 O with oxidation of GSH (20) and plays a crucial role in LV remodeling and failure after myocardial infarction (30). Some studies reported increased activity of myocardial enzymatic antioxidants in ischemia-reperfusion (1), whereas other studies reported decreased (10,27) or unchanged (7,37) activity.…”
Section: Discussionmentioning
confidence: 96%
“…Thus the changes in GPX activity were not likely the major determinant of preserved GSH levels in the present study. GSH is enzymatically synthesized and degraded (20). The changes in metabolic pathways of GSH may facilitate preservation of GSH levels during ischemia-reperfusion in the presence of enhanced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%